Exploring Farmers’ Perception and Constraints on the Adoption of Small-Scale Irrigation in Hulet Eju Enesie District, North-Western Ethiopia - Getasew Daru; Sinkie Alemu (Advances in Agriculture)
Irrigation farming is one approach to reduce climate-related risks, and make production possible throughout the year. Nevertheless, farmers were limited to using small-scale irrigation (SSI) in the study area. This study mainly analyzed the perception of farmers’ and their constraints to use irrigation. The study used a multistage sampling technique to collect the primary data from 102 nonuser and 82 irrigation user respondents. Likert rating scale, relative importance index (RII), and descriptive statistics were used to analyze the data. The result of the RII indicates that, irrigation ensures high-net income (0.87), high-market demand for products (0.84), and insurance against drought (0.82) were highly perceived as advantageous attributes of the irrigation. Whereas, production cost (0.85), skill requirements (0.74), and declining soil fertility (0.65) were strongly perceived as relative disadvantage attributes of irrigation. Plant disease, input shortages, ineffective water distribution, and poor transportation are identified as major constraints for farmers to practice irrigation. Overall, farmers commonly noted the importance of irrigation. However, irrigation users highly perceived the positive attributes; whereas nonusers extremely perceived the negative attributes of irrigation. This implies the existence of perception differences between the two groups of farmers. Therefore, concerned stakeholders should strive to close the perception gap toward irrigation through interventions.